Four new species of the frogmouth genus Chaunax (Lophiiformes: Chaunacidae) from Taiwan and the Philippines - Ho, Hsuan-Ching; Ma, Wen-Chun (Zootaxa, 2022)
Four new species of the genus Chaunax found in Taiwan and the Philippines are described. Chaunax albatrossae sp. nov. belongs to the C. abei species group and is distinct from its congeners in having a dark gray mouth cavity, a dark brown to black gill chamber and gill rakers and skin covered with only short, simple spinules. Three new species belong to the C. fimbriatus species group: Chaunax erythraeus sp. nov. is distinct in having a uniformly pinkish-red body and an entirely black gill chamber; Chaunax obscurus sp. nov. is distinct in having a dark gray mouth cavity and orange-red marbling on the dorsal surface that fades after fixation; and Chaunax viridiretis sp. nov. is distinguished by its green reticulate pattern with some small, bright-white patches on the dorsal surface. The diagnostic characters used to identify the chaunacids are summarized and a key to all Chaunax species found in Taiwan and adjacent waters is provided.